Effect of anthropogenic noise on call parameters of Hyla arborea (Anura: Hylidae) - Lukanov, Simeon; Naumov, Borislav (Ecological Questions, 2019)
Increasing urbanisation in recent decades has subjected many species and their populations to the influence of anthropogenic noise generated by human technologies. Noise pollution can negatively affect acoustic communication in representatives of different taxa and frogs, as the most vocally active amphibians, are especially vulnerable to such adverse effects. In the present study, we tested the hypothesis that anthropogenic noise could alter the mating call parameters in the European treefrog. The two chosen study sites were in the same geographic area and had similar characteristics except for the presence of anthropogenic noise source. Recordings were made in a WAV-PCM format and both spectral and temporal call parameters were analysed using specialised software. Results demonstrated significant differences in most of the studied parameters, suggesting that treefrogs are able to alter their calls and communicate successfully in moderate levels of anthropogenic noise.